Assessing the causal association of glycine with risk of cardio-metabolic diseases - Laura B. L. Wittemans (Nature Portfolio, 2019)
Epidemiological studies have associated circulating levels of the amino acid glycine with cardiometabolic outcomes. Here, in a genome-wide meta-analysis of 80,003 individuals, Wittemans et al. identify 22 novel genetic loci for glycine and find a causal relationship with coronary heart disease using MR.